2020
DOI: 10.1371/journal.pone.0241805
|View full text |Cite
|
Sign up to set email alerts
|

Toxicodendron vernicifluum Stokes extract inhibits solid tumor growth and lung metastasis of 4T1 murine mammary carcinoma cells in BALB/c mice

Abstract: Toxicodendron vernicifluum Stokes has long been used as a food supplement and traditional herbal medicine in East Asia. We applied a new extraction method to produce Toxicodendron vernicifluum Stokes extract (TVSE), that doesn’t contain urushiol (an allergenic toxin) but dose have higher levels of some flavonoids such as fustin and fisetin. This study was conducted to investigate the anticancer effects of TVSE in an in vivo system. Fifty BALB/c mice were acclimated for one week and then injected with 4T1 murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Lee et al elucidated that Toxicodendron vernicifluum stokes extract (TVSE) suppressed not only the growth of solid tumors in breast itself but also the metastasis to lung in 4T1-injected mice. While decrease in Ki67 implied the inhibition of proliferation, transcriptional alternation of several genes such as MMP-2, TIMP-1, uPA, intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), and plasminogen activator inhibitor 1 (PAI-1) played key roles in suppressing metastasis [ 122 ]. Yue et al invented an innovative herbal formula for reducing tumor growth and extending the life span of breast cancer model.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al elucidated that Toxicodendron vernicifluum stokes extract (TVSE) suppressed not only the growth of solid tumors in breast itself but also the metastasis to lung in 4T1-injected mice. While decrease in Ki67 implied the inhibition of proliferation, transcriptional alternation of several genes such as MMP-2, TIMP-1, uPA, intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), and plasminogen activator inhibitor 1 (PAI-1) played key roles in suppressing metastasis [ 122 ]. Yue et al invented an innovative herbal formula for reducing tumor growth and extending the life span of breast cancer model.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has suggested that this extract, containing 29% fustin without urushiol (a toxic compound in T. vernicifluum), shows modest anticancer effects on lung metastasis of 4T1 murine mammary carcinoma in an in vivo mouse model. 34 However, the efficacy of this extract is markedly limited (200 mg/kg administration induced 10% suppression of tumor volume), and its underlying mechanisms remain poorly understood.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In MCF‐7 cells, fisetin inhibited PKCα/ROS/ERK1/2, p38 MAPK, and nuclear factor‐κB (NF‐κB) signaling, which has led to the downregulation of MMP‐9 expression (Noh et al, 2015). In addition, in vivo study showed that fisetin could significantly diminish the growth of primary breast tumor concurrent with decreased lung metastasis incidence (Lee et al, 2020).…”
Section: Anticancer Activity Of Fisetinmentioning
confidence: 99%